Proses Penanganan Perkara Pidana Pencurian Pretima di Kabupaten Gianyar - Gede Agus Antonio Leovandy; Anak Agung Sagung Laksmi Dewi (Jurnal Konstruksi Hukum, 2022)
Pretima theft not only causes property losses but also non-material losses such as trust which results in disruption of the spiritual balance of Hindu society. This kind of action is a crime that is very, very detrimental to Hindus, especially in Bali because they are considered to have damaged the beliefs of people's lives. The defendants are also considered to have tarnished the local customary rules contained in awig-awig in Bali. Therefore, the purpose of this study is to discuss the process of handling the criminal case of Pretima theft in Gianyar Regency and to examine the obstacles in the process of handling the Pretima theft crime in Gianyar Regency. The type of research used is empirical research. In this research, a sociological approach is used, a legislative approach, a conceptual approach, a case approach. The results of this study indicate that the process of handling the criminal case of Pretima theft in Gianyar Regency, namely carrying out special operations such as brush operations, concentrated and so on outside of daily routine activities, is given heavy legal sanctions. may be subject to customary sanctions: A cleaning ceremony (purification) is held, a fine in the form of money; and Also dismissed as a member of the indigenous community. Obstacles in the process of handling the crime of Pretima theft in Gianyar Regency, among others, the lack of maximum supervision of sacred objects at temples in each traditional village in Gianyar Regency, the lack of witnesses so that it is difficult to find evidence, inadequate facilities and infrastructure.